2008
DOI: 10.4306/pi.2008.5.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B Levels and Major Depressive Disorder: Its Characteristics and Role in Antidepressant Response

Abstract: ObjectiveS100B is a neurotrophic factor that is involved in neuroplasticity. Neuroplasticity is disrupted in depression; however, treatment with antidepressants can restore neuroplasticity. S100B has previously been used as a biological marker for neuropathology and neuroplasticity; therefore, in this study, we compared serum S100B levels in depressive patients to those of normal controls. In addition, we compared the serum S100B levels of antidepressant responders to those of nonresponders.MethodsThirty five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 38 publications
2
41
1
Order By: Relevance
“…As previously reported, participants who did not provide plasma samples in CO-MED trial were younger and had lower use of statin medication than those who provided plasma samples at baseline, but did not differ on any other baseline clinical and sociodemographic features [12]. Additionally, as participation in the continuation-phase of CO-MED was censured for those participants with inadequate response [32], only acute-phase visits (baseline and weeks 1, 2, 4, 6, 8, 10, and 12) were included in this report. The CO-MED trial used broad inclusion and exclusion criteria, (fully listed at https://clinicaltrials.gov/ct2/show/NCT00590863) while recruiting from psychiatric and primary care clinics that were chosen to ensure adequate minority representation and a diverse participant group [32].…”
Section: Study Overviewmentioning
confidence: 64%
See 2 more Smart Citations
“…As previously reported, participants who did not provide plasma samples in CO-MED trial were younger and had lower use of statin medication than those who provided plasma samples at baseline, but did not differ on any other baseline clinical and sociodemographic features [12]. Additionally, as participation in the continuation-phase of CO-MED was censured for those participants with inadequate response [32], only acute-phase visits (baseline and weeks 1, 2, 4, 6, 8, 10, and 12) were included in this report. The CO-MED trial used broad inclusion and exclusion criteria, (fully listed at https://clinicaltrials.gov/ct2/show/NCT00590863) while recruiting from psychiatric and primary care clinics that were chosen to ensure adequate minority representation and a diverse participant group [32].…”
Section: Study Overviewmentioning
confidence: 64%
“…Data for this report were obtained from the CO-MED trial where participants (n = 665) were randomized after stratification for site to one of the following treatment arms: escitalopram plus placebo, bupropion sustained-release (SR) plus escitalopram, and venlafaxine extended-release (XR) plus mirtazapine [32]. The analytic sample of this report (n = 153) includes a sub-set of CO-MED trial participants who provided plasma samples at baseline as part of a separate add-on optional biomarker study that required an additional consent.…”
Section: Study Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the severity of depression was positively correlated with serum S100B levels and with treatment response following 4 weeks of treatment (Schroeter et al., 2002; Arolt et al., 2003). Of interest, another study reported similar baseline levels of serum S100B in depressed patients and in control groups, however, found higher baseline levels to be predictive for treatment response to antidepressants (Jang et al., 2008).…”
Section: Mental Disordersmentioning
confidence: 99%
“…SB100B is a protein associated with MDD which is expressed and secreted by glial cells and other nonneural cell lineages implicated in synaptogenesis and neuronal survival [92]. A number of recent studies have observed that SB100B is increased in the hippocampus, serum, and cerebrospinal fluid of MDD patients, most likely reflecting a response of glial cells to neural damage (see [93] and references therein) and also that the basal levels of serum may predict the outcome of the therapeutic response to antidepressants [94]. …”
Section: Concluding Remarks: Adult Neurogenesis and Mddmentioning
confidence: 99%